Studi Kontribusi Workplace Spirituality terhadap Affective Well-being Karyawan Restoran Cepat Saji di Kota Bandung - Safira Nura Hanjani; Ali Mubarak (UNISBA Press, 2024)
Abstract. Workplace spirituality is defined as something at employee’s workplace related to employee’s perception about meaningful work, sense of community, and alignment with organizational values (Milliman et al., 200316). Van Katwyk et al. (2000)4 defined affective well-being as employee’s affection about their job and how their affective responds towards their job. This study aims to know how workplace spirituality contributes to fast food workers’ affective well-being. This study is a quantitative study and used multiple regression analysis. The subject of this study are 98 shift workers working as crew store in a fast-food-chains in Bandung, Indonesia. The sample are measured by non-probability sampling using convenience sampling method. Workplace Spirituality Scale by Milliman et al. (2018)15 and Job-related Affective Well-being Scale by Van Katwyk et al. (2000)4 that were adapted to Indonesian by Permana and Prakoso (2022)12 are used for the instrument. This study found that workplace spirituality has 46.1% significant contribution to affective well-being, with sense of community has the highest contribution (19%), then alignment with organizational values (15.2%), and lastly meaningful work (11.9%). Abstrak. Workplace spirituality didefinisikan sebagai sesuatu di tempat kerja karyawan yang berkaitan dengan persepsi karyawan mengenai meaningful work, sense of community, dan alignment with organizational values (Milliman et al., 200316). Affective well-being menurut Van Katwyk et al. (2000)4 adalah perasaan karyawan akan pekerjaannya dan bagaimana respon perasaan karyawan terhadap pekerjaannya. Penelitian ini bertujuan untuk mengetahui bagaimana kontribusi workplace spirituality terhadap affective well-being karyawan restoran cepat saji. Metode penelitian yang digunakan adalah kuantitatif dengan teknik analisis regresi berganda. Partisipan dalam penelitian ini sebanyak 98 orang crew store yang bekerja secara shift di restoran cepat saji di Kota Bandung, yang didapatkan dengan teknik non-probability sampling menggunakan metode convenience sampling. Alat ukur yang digunakan adalah Workplace Spirituality Scale dari Milliman et al. (2018)15 dan Job-related Affective Well-being Scale dari Van Katwyk et al. (2000)4 yang keduanya telah diadaptasi oleh Permana dan Prakoso (2022)12. Penelitian ini menemukan bahwa workplace spirituality memiliki kontribusi yang signifikan sebesar 46.1% terhadap affective well-being, dengan aspek sense of community yang paling tinggi kontribusinya (19%), diikuti alignment with organizational values (15.2%), dan meaningful work (11.9%).